Impact of Accounting Process Digitalization on the Efficiency of Regional Financial Reporting - Ceci Rampe; Rahmawati Rahmawati; Antong Antong (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the influence of digital record-keeping, digital reporting, and system integration on the efficiency of financial statements in BPKAD Palopo City. Methodology: The method used is quantitative with a survey approach using questionnaires. The data were analyzed using multiple linear regression. Results: The results of the study show that digital recording and digital reporting have a positive and significant effect on the efficiency of financial statements. However, system integration did not show a significant impact. Findings: The findings recommend digital system optimization as well as training for employees to improve the efficiency of regional financial reporting. Novelty & Originality: The novelty of this study lies in its focus on the simultaneous examination of digital recording, reporting, and system integration in a local government financial agency in Palopo City, a context rarely explored in prior research. Its originality emerges from the empirical testing of these variables within the public sector accounting environment. Conclusions: The implications of this study show that the success of accounting digitization is highly dependent on the readiness of the infrastructure and the competence of the human resources that operate the digital system. Type of Paper: This paper is an empirical research paper.